2017
DOI: 10.14569/ijacsa.2017.080830
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning Application Development for Improvement of English Listening Comprehension

Abstract: Abstract-Trend towards English language learning has been increased because it is considered as Lingua franca i.e. language of communication for all. However students of Pakistan are behind in this pace, especially rural elementary students. In rural areas there is crucial need to get assistance in their own curriculum after school because mostly they do not find anyone to help at home. M-Learning (Mobile Learning) assists learning anywhere and anytime. This ubiquitous power of M-Learning helps in after school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…From the results illustrated in the table (3) the highest mean score (3.62) was obtained for item st13, "Using Telegram makes the learning of reading skill more fun." This finding proved by Laghari et al (2017) who concluded that students were happy, excited, and motivated to learn via M-learning application.…”
Section: Discussionmentioning
confidence: 68%
“…From the results illustrated in the table (3) the highest mean score (3.62) was obtained for item st13, "Using Telegram makes the learning of reading skill more fun." This finding proved by Laghari et al (2017) who concluded that students were happy, excited, and motivated to learn via M-learning application.…”
Section: Discussionmentioning
confidence: 68%
“…This finding supports the previous research on developing a Mobile-Assisted Language Learning Application (MALL) for English Intensive Course (IC) (Rohandi et al, 2017) confirming that the MALL application is useful and helpful for students to increase their motivation in understanding the materials of IC textbook. Our study is also in line with Ubiquitous Fitness English Listening Comprehension System (UFELCS) designed by Liu et al (2018) incorporating collaborative listening activities into a fitness center, a media made by Utami et al, (2021) developing E-Learning with Schoology in hybrid learning strategy in listening skill of Tadulako University, the website (ELLLO -English Listening Lesson Library Online, n.d.), the use of ELLO in Improving in Teaching Listening to Students (Hadi et al, 2021), M-Learning application developed by Parveen et al (2017) for rural primary students in Pakistan, a smartphone application evaluating music listening habits for 35 days, and also research-based listening materials utilizing multimedia for seventh-grade students of lower secondary schools developed by Rakhmawati et al (2016) using CD/DVD/flash disk format employing Text-to-Speech and Audacity software and a computer installed an additional software named macromedia flash CS6. They claimed that the usefulness of their product is to develop the students' motivation to learn while providing a prototype of supplementary listening materials for English textbook using Curriculum 2013 which has no listening practices within.…”
Section: Discussionmentioning
confidence: 99%